Influence of various cleaning solutions on the geometry, roughness, gloss, hardness, and flexural strength of 3D-printed zirconia - HongXin Cai; Min-Yong Lee; Heng Bo Jiang; Jae-Sung Kwon (Scientific Reports, 2024)
Abstract This study aimed to investigate the impact of various cleaning solutions on the geometry, roughness, gloss, hardness, and flexural strength of 3D-printed zirconia. Cleaning solutions, including isopropyl alcohol (IPA, 99.9%), ethyl alcohol (EtOH, 99.9%), and tripropylene glycol monomethyl ether (TPM, ≥ 97.5%), were diluted to a concentration of 70% and categorized into six groups: IPA99, EtOH99, TPM97, IPA70, EtOH70, and TPM70. Zirconia discs, printed via digital light processing, were sintered after cleaning. The geometry, roughness, gloss, hardness, and flexural strength were analyzed. Statistical analysis was performed using one-way ANOVA with Tukey’s post hoc test (p < 0.05). The thickness of TPM70 was the highest. The diameter of TPM70 was significantly larger than that of EtOH99 and IPA70 (p < 0.05). The weight of the TPM groups was significantly higher than that of IPA70 (p < 0.05). The roughness Ra of TPM70 was significantly greater than that of IPA99, EtOH99, and EtOH70 (p < 0.05). The differences in surface gloss, hardness, and flexural strength among the different groups were not statistically significant (p > 0.05). Different cleaning solutions did not affect the surface gloss, hardness, and flexural strength of 3D-printed zirconia. High and low concentrations of the same cleaning solution did not affect the surface gloss, hardness, and flexural strength. IPA70, TPM97, and EtOH can be considered viable post-printing cleaning alternatives to the traditional gold standard, IPA99.